Enhanced medical image analysis: leveraging CUDA for fast and accurate Pneumonia detection with optimized CNNs - Alvi, Md.Waseq Alauddin (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2024.